MAGNETIC FIELD INFLUENCE TECHNOLOGIES ON HIGH-PARAFFIN CRUDE OIL IN THE PIPELINE WITH DIFFERENT CALIBER - Nalyvaiko, O. I.; Vynnykov, Yu. L.; Nalyvaiko, L. G.; Petrash, R. V.; Ichanska, N. V.; Chyhyriov, V. V. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Influence technology of constant magnetic field at high paraffin oil is enhanced to prevent the formation and wax deposition in the tubing and during oil transportation by pipelines of different calibres. Action mechanism determination of directed static magnetic field on high- viscosity paraffin oil wells in Boryslav deposits was investigated by conducting laboratory tests of samples. For Botyslav field conditions the construction of magnetic recovery equipment (MRE) regarding the influence of magnetic induction on heavy oil deposits is designed.
Keywords: paraffin; oil; magnetic induction; well; oil field